Effects of high-pressure activated slightly acidic electrolyzed water on cleaning and sterilization of pig transfer vehicles - Zhao, Xuedong; Tao, Shengnan; Qi, Fei; Li, Hao; Shi, Zhengxiang (International Journal of Agricultural and Biological Engineering, 2024)
The establishment of biosafety system is of enormous importance to the livestock and poultry production in terms of mitigating the transmission of diseases and implementing regional prevention and control measures. However, the current sterilization technology presents several drawbacks, including time-consuming procedures, chemical residues, and challenges in treating the sewage after rinsing. In this study, a novel cleaning and sterilization method that combines slightly acidic electrolyzed water and high pressure water-jet was developed. An orthogonal test was conducted to examine the correlation between high-pressure conditions and the various non-structural parameters on the efficacy of sterilization rate. In a field test, the effectiveness of the technology in cleaning pig transfer vehicles was evaluated by the total plate count and variations of community composition. The findings revealed that the combination of process parameters, including an available chlorine concentration of 200 mg/L, rinsing pressure of 170 bar, rinsing duration of 10 s, and residence time of 15 min, resulted in a removal rate of colony concentration on the surface of pig transfer vehicles of (96.50±0.91)%. Moreover, it was demonstrated to effectively inhibit a variety of pathogenic bacteria. The innovative cleaning system has the potential to replace traditional methods and reduces pollution while saving time and labor. It introduces a novel approach for sterilization of transportation in livestock and poultry farms as well as the biosafety construction of the animal husbandry. [Key words: slightly acidic electrolyzed water; high pressure water-jet; sterilization; biosafety; concentrated animal productionDOI: 10.25165/j.ijabe.20241704.8847Citation: Zhao X D, Tao S N, Qi F, Li H, Shi Z X. Effects of high-pressure activated slightly acidic electrolyzed water on cleaning and sterilization of pig transfer vehicles. Int J Agric & Biol Eng, 2024; 17(4): 53–59.